Analysis of Trust in B2B Relationships: The case of automatic storage and retrieval systems - Alves, Vitor (2017)
This paper emphasizes the role that trust plays in the success of B2B relationships providing a model and contributing to improve the relationship between buyers and suppliers in the sector of automatic storage and retrieval systems. Relationships between a large global manufacturer and supplier of storage and retrieval systems and their major Portuguese references are studied. A questionnaire has been applied and the opinion of administrators/buyers of such systems, directors and logistics managers and finally supervisors and managers of the logistics or production system were collected in order to obtain the necessary information to assess whether trust contributes to the success of B2B relationships. The results introduced new determinant factors for success in B2B relationships and gave rise to a new model that resulted from the exploratory factor analysis. The authors conclude that trust is associated with confidentiality, as well as with the assistance provided by the supplier which is highly valued in a B2B relationship and contributes to improving the relationship between buyers and suppliers. Little research has been done in the area of B2B relationships, in what concerns to the specific role that trust plays in the success of B2B relationships in the sector of automated storage and retrieval systems. This paper emphasizes the role that trust plays in these types of relationships, by providing a model and contributing to improve the relationship between buyers and suppliers.Keywords ASRS; WMS; B2B; Trust; Benevolence; Honesty; Competence; Success of B2B relationship; Satisfaction; Purchase intention.Paper type Research paper